1977
DOI: 10.1111/j.1528-1157.1977.tb04468.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Testing of Valproic Acid Compared to Ethosuximide in Monkey Model: II. Seizure, EEG, and Diurnal Variations

Abstract: Summary The efficacy of valproic acid (VPA) compared t o ethosuximide (ESM) was tested in an alumina‐gel monkey model (N= 12) in‐ strumented with indwelling catheters (for drug infusion and blood sampling) and an EEG plug (for sleep staging and spike recording). The results indicated that VPA was effective in the plasma level range 50‐ 150μg/ml in terms of seizure frequency, duration, and severity, as well as EEG sharp activity. However, focal seizures were not attenuated until the higher plasma concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 14 publications
1
10
1
Order By: Relevance
“…Seizure frequency was reduced with high doses of VPA or CZP, even after cessation of the ASM. The enduring effects of VPA after medication discontinuation were first demonstrated in this primate model . These studies established ASM efficacy for seizure prophylaxis and suggest that long‐term risk modification requires high doses.…”
Section: Results: Nonhuman Primate Models Of Epilepsymentioning
confidence: 65%
See 3 more Smart Citations
“…Seizure frequency was reduced with high doses of VPA or CZP, even after cessation of the ASM. The enduring effects of VPA after medication discontinuation were first demonstrated in this primate model . These studies established ASM efficacy for seizure prophylaxis and suggest that long‐term risk modification requires high doses.…”
Section: Results: Nonhuman Primate Models Of Epilepsymentioning
confidence: 65%
“…Animals given pharmacologic prophylaxis had only partial seizures, whereas control animals exhibited secondarily generalized tonic‐clonic seizures (GTCS). This model compared the efficacy of valproic acid (VPA) and ethosuximide (ESM) . Low‐dose VPA reduced seizure frequency, duration, and severity but a higher dose was required to attenuate focal motor seizures.…”
Section: Results: Nonhuman Primate Models Of Epilepsymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to different seizure or epilepsy models in rodent species, larger mammalian species, including dogs and rhesus monkeys, have been used by some researchers to evaluate whether tolerance to AEDs develops during prolonged treatment. In an alumina-gel monkey model, Lockard et al (62) reported that VPA was effective in the plasma-level range of 50-150 μg/ml with an immediate but transitory effect of VPA on seizure frequency at low plasma levels, and a more permanent decrease in seizure frequency at the higher plasma levels. These data substantiate that tolerance to VPA occurs in some models, depending on the doses or plasma drug levels being studied.…”
Section: Demonstration Of Tolerance To Aeds In Different Models and Smentioning
confidence: 99%